Autonomy and professional identity formation in residency training: A qualitative study. Issue 7 (26th March 2020) - Sawatsky, Adam P.; Santivasi, Wil L.; Nordhues, Hannah C.; Vaa, Brianna E.; Ratelle, John T.; Beckman, Thomas J.; Hafferty, Frederic W.
Abstract: Context: Professional identity formation (PIF) involves the development of professional values, actions and aspirations and is central to medical education. Current understanding of PIF is informed by psychological and sociological theories. One ideal of medicine is responsibility to the patient; the development of this ideal is related to learner autonomy. The purpose of this study was to further theorise the relationships between the individual and contextual aspects of PIF through exploring the associations amongst autonomy, making decisions and responsibility for patients during residency training. Methods: Using constructivist grounded theory, we conducted 23 semi‐structured interviews with internal medicine residents at an academic medical centre. Interview transcripts were de‐identified and processed through open coding and analytic memo writing. During data collection and analysis, we identified social cognitive theory (SCT), specifically reciprocal determinism, or the triadic and reciprocal relationship between context, person and behaviour, as a useful theoretical lens through which to illuminate the relationship between autonomy and PIF. Using SCT to guide analysis, we organised themes, identified relationships amongst themes, and refined them through group discussion and constant comparison with new data. Results: Residents discussed three main themes: autonomy; making decisions, and responsibility for patient care. Autonomy allowed residents to feel personally responsible for patient care, and build confidence and trust. Autonomy allowed residents to feel engaged in making 'real decisions' for patient care. By displaying confidence in their decision making, residents were granted more autonomy. Lack of autonomy led to disengagement and lack of ownership over patient care. Conclusions: This study highlighted the role of autonomy in the PIF of learners. Exploring the tension between autonomy and supervision through the lens of SCT highlighted the interconnectedness of context, behaviour and identity in PIF. To ensure optimal learning environments for PIF, educators should weigh the need for autonomy against the demands for supervision and patient safety. Abstract : The authors use Social Cognitive Theory to describe professional identity formation in residency training, highlighting the relationship between autonomy, making decisions, responsibility for patients.